Risk factors for placental malaria and associated adverse pregnancy outcomes in Rufiji, Tanzania: a hospital based cross sectional study - Ndeserua, Rabi (Afr Health Sci, 2015)
BACKGROUND: Prevention and treatment of malaria during pregnancy is crucial for reduction of malaria in pregnancy and its adverse outcomes. The spread of parasite resistance to Sulphadoxine-Pyrimethamine (SP) used for Intermittent Preventive Treatment for malaria in pregnancy (IPTp), particularly in East Africa has raised concerns about the usefulness and the reliability of the IPTp regimen. We aimed to assess the effectiveness of two doses of SP in treating and preventing occurrence of adverse pregnancy outcomes. METHODOLOGY: The study was an analytical cross sectional study which enrolled 350 pregnant women from Kibiti Health Centre, South Eastern Tanzania. Structured questionnaires were used to obtain previous obstetrics and medical history of participants and verified by reviewing antenatal clinic cards. Maternal placental blood samples for microscopic examination of malaria parasites were collected after delivery. Data was analyzed for associations between SP dosage, risk for PM and pregnancy outcome. Sample size was estimated based on precision RESULTS: Prevalence of placental maternal (PM) was 8% among pregnant women (95%CI, 4.4–13.1%). Factors associated with increased risk of PM were primigravidity (P<0.001) and history of fever during pregnancy (P= 0.02). Use of at least 2 doses of SP for IPTp during pregnancy was insignificantly associated with reducing the risk PM (P=0.08), low birth weight (P=0.73) and maternal anemia (P=0.71) but associated significantly with reducing the risk of preterm birth (P<0.001). CONCLUSION: Two doses of SP for IPTp regime are ineffective in preventing and treating PM and adverse pregnancy outcome. Hence a review to the current IPTp regimen should be considered with possibility of integrating it with other malaria control strategies.